An approach for malware behavior identification and classification - Zolkipli, Mohamad Fadli; Jantan, Aman (2011 3rd International Conference on Computer Research and Development, 2011)
Malware is one of the major security threats that can break computer operation. However, commercial anti-virus or anti-spyware that used signature-based matching to detects malware cannot solve that kind of threats. Nowadays malware writers try to avoid detection by using several techniques such as polymorphic, metamorphic and also hiding technique. In order to overcome that issue, we proposed a new framework for malware behavior identification and classification that apply dynamic approach. This framework consists of two major processes such as behavior identification and malware classification. These two major processes will integrate together as interrelated process in our proposed framework. Result from this study is a new framework that able to identify and classify malware based on it behaviors.